2012
DOI: 10.1097/ta.0b013e31823d0f03
|View full text |Cite
|
Sign up to set email alerts
|

Evolving role of endovascular techniques for traumatic vascular injury

Abstract: ENDO procedures for arterial injury have increased over time while mortality for arterial injury subtypes has significantly decreased. Early ENDO procedures are common and are independently associated with a lower risk of mortality. These results suggest outcomes after vascular injury may benefit from ENDO expertise and that ENDO techniques should be incorporated into the early treatment algorithm of trauma patients with vascular injury, particularly those that require difficult operative exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 17 publications
2
34
0
Order By: Relevance
“…There were important ongoing temporal trends with increasing endovascular therapy utilization for both blunt and penetrating arterial trauma. 36 Interestingly, when evaluated across the racial groups, the rate of adoption of endovascular therapy appeared similar for black and Hispanic patients when compared to white patients for both blunt and penetrating injuries. Thus, disparities in access to new technologies do not appear to explain racial differences in outcomes in arterial injury.…”
Section: Discussionmentioning
confidence: 94%
“…There were important ongoing temporal trends with increasing endovascular therapy utilization for both blunt and penetrating arterial trauma. 36 Interestingly, when evaluated across the racial groups, the rate of adoption of endovascular therapy appeared similar for black and Hispanic patients when compared to white patients for both blunt and penetrating injuries. Thus, disparities in access to new technologies do not appear to explain racial differences in outcomes in arterial injury.…”
Section: Discussionmentioning
confidence: 94%
“…31,32 There are a number of new training courses designed to familiarize providers with the emergent use of REBOA and other endovascular skills. 31,32 There are a number of new training courses designed to familiarize providers with the emergent use of REBOA and other endovascular skills.…”
Section: Discussionmentioning
confidence: 99%
“…[89][90][91] A recent report using the National Trauma Databank (NTDB) showed an increase in endovascular procedures for vascular trauma from 1% of cases in 2002 to nearly 11% in 2008. 92 This same study also showed an independent risk reduction in mortality for subclavian injuries treated with endovascular techniques when analysis was controlled for major confounders. Additional recent work has shown that nearly 6% of all peripheral vascular injuries from 2007 to 2009 reported to the NTDB were approached with an endovascular technique as the initial procedure of choice.…”
Section: New Horizons In Endovascular Approaches For Vascular Traumamentioning
confidence: 80%
“…93 Injuries were also able to be addressed early (<24 hours) in the hospital course even in more severely injured patients. 92 Beyond uses in thoracic aortic trauma, the most literature exists for extension of endovascular repair for subclavian and axillary artery injuries (Fig. 6).…”
Section: New Horizons In Endovascular Approaches For Vascular Traumamentioning
confidence: 99%
See 1 more Smart Citation